Perancangan Sistem Pendukung Keputusan Menentukan Kualitas Beras dengan Menggunakan Metode Weighted Product - Syafi'ul Marom; Harunur Rosyid (Jurnal Teknika, 2022)
One of the food commodities that is the dominant food ingredient in almost all Asian countries is rice, especially for countries in the Southeast Asia Region. The high demand for quality rice by consumers makes it difficult for companies to determine the best rice criteria. In determining the best quality of rice, a method is needed to determine the quality of rice, namely the decision support system method with the WP (weighted product) method. This method uses the multiplication of attribute branches, where the attribute is raised to the power of the weight of the attribute in question. Based on the results of research on the quality of rice at UD. Cahaya Makmur, then we need criteria such as color, cleanliness, size, aroma, and texture, so that it will get the best quality rice, in a decision support system using the WP (weighted product) method, it results in a ranking of the best rice quality alternatives. V value 0.2754, the second rice 42 V value 0.2526, the third serang rice V 0.2406, the fourth Konga rice V 0.2315.Â